Estructura funcional de comunidades de bromeliáceas con énfasis en el flujo de Metano, Agua y Nutrientes a lo largo de la gradiente altitudinal de la cuenca Amazónica Ecuatoriana - Jaramillo Díaz, Nelson Armando (2015)
This study was carried out in order to determine the functional structure of bromeliad communities focusing on the flow of methane (CH4), water and nutrients along the altitudinal gradient in the provinces of Loja, Zamora, Napo and Orellana. This was carried out during May 2012 to August 2014. A total of 72 temporary sample plots measuring 20 x 20 m (400 m2) were set up, where parameters of diversity, abundance, and functional differentiation were displayed by the bromeliads in relation to their architecture.In their interior (phytotelm) several processes and interactions are performedsuch as methane emissions, water storage, biomass content and concentration of nutrients (N and P) whose values were extrapolated to that of a hectare of forest. The study found that the most diverse sites in terms of morphospecies were San Francisco with 24 morphospecies and Cajanuma with 16 morphospecies in the southern region (RS) and 14 morphospecies in Guacamayos in the northern region (RN). The greatest number of bromeliads were found in San Francisco (RS) with 7446 specimens and in Guacamayos (RN) with 3177 specimens. A grand total of 9 functional types of bromeliads for the Ecuadorian Amazon basin were established. The largest methane emission estimates are given in San Francisco in the South Region (RS) 4261.15 mg/ha and macaws and the Northern Region (RN) 3 994.48 mg/ha. Most water storage tanks bromeliads is in San Francisco sites (RS) 11 687.58 l/ha and macaws (RN) 8 152.42 l/ha. Sites that show larger amounts of biomass are bromeliads San Francisco (RS) with 540.57 kg/ha and macaws with 452.71 kg/ha. Sites with high concentrations of nitrogen nutrients are San Francisco with 97.61 kg/ha, followed by Cajanuma with 68.09 kg/ha and macaws with 60 Kg/ ha; for phosphorus you have to San Francisco with 94.51 kg/ha, Cajanuma 67.20 kg/ha and macaws with 57.26 kg/ha . The results of this study indicated that the sites located at 2000 m s.n.m. exhibited better results with respect to morphotype diversity, abundance, methane emissions, water storage, amount of biomass and nutrient concentrations (N and P) according the functional types bromeliads.